(untitled) (Actual Problems of Psychology in Educational Institutions, 2015)
Our society has always been interested in the ability of understanding the inner world of a person by means of external manifestations. That is why a great number of different researches concerning connection of nonverbal signs, handwriting, body structure with individual characteristics, peculiarities of their tempers (especially character accentuations) were found. Thus, for example, Eugene LeDonne proposed the theory that was based on the similarity of different types of the body constitutions with five geometrical figures - a quadrangle, a triangle, a circle, an oval and a cone [1]. However, in spite of sufficient use of similar achievements (particularly Sheldon’s or Kretschmer’s constitutional theories of a personality), they bear only approximate facts and require some additional sources of information about the individual peculiarities. Preferences in the personal choice of clothing style, colour (that a person chooses consciously and forms during some period of time) can also give some definite information about a personality, his or her character. As we are future employees in the social sphere of the relationships «Person-to-Person», it is very important for us to acquire a significant skill to notice allusions to definite characterological differences in «signs» of clothing and its colours.